PENGARUH PEMBEBANAN OVERLOAD BUCKET TERHADAP KEKUATAN MATERIAL KOMPONEN ARM PADA EXCAVATOR VOLVO EC700B TIPE CRAWLER - Lia Pongsapan (TRANSMISI, 2016)
Volvo Excavator EC700B crawler type used in coal mining to remove coal and top soil. The maximum capacity of the bucket according to the standard Volvo Construction Equipment is 8.28 tonnes, but the actual experience in the field bucket overloaded with cargo capacity increased to 12.14 tonnes. This study analyzes the components of arm strength when holding the bucket on the working conditions of overload. Materials made of ASTM A36 arm with allowable stress limit (yielding point) of 290 N / mm2. The results showed the increase in value of the force and stress on the arm component loading conditions overload at 28-32% of normal loading conditions. The maximum voltage occurs at the bracket arm hydraulic cylinder that is equal to 150.4 N / mm2. The voltage value is smaller than the allowable stress of material, so the material at arm component complies with the standards of eligibility and declared safe.